Comparación de la prevalencia y severidad de caries y su relación con estilo de vida en instituciones educativas de la comuna 4 de Ibagué 2019 (2020)
Introduction: caries in childhood is a disease of multifactorial etiology that affects preschool children, it is evolutionary and that without the care and control of the factors that produce it, it reaches the destruction of the teeth causing pain, discomfort, suffering, affecting the People's lives and its consequences include a high risk of new injuries in both temporary and permanent dentition. Objective: to establish the prevalence of caries in children from 2 to 5 years of age in small ventures and rainbow educational institutions, to determine the degree of caries severity according to icdas. Methodology: descriptive cross-sectional study in children of the Center for Child Development Educational Little Adventures and Rainbow. of the commune # 4 of Ibagué Tolima 2019, between 2 to 5 years old. The population consisted of 94 children from which the stratified random sample with all the schoolchildren will be extracted, after prior informed consent signed by the parents, a complete oral examination will be performed on the children of the child development center with natural light and with the aid of dental mirror and exploration probe in a non-invasive way, to determine the severity of caries according to ICDAS. Result: it was determined that there is no association between the presence of caries and the impacts of lifestyle. Conclusions: a small group expressed impact of oral health condition related to lifestyle.